Dryland Watershed Restoration With Rock Detention Structures: A Nature-based Solution to Mitigate Drought, Erosion, Flooding, and Atmospheric Carbon - Gooden, Jennifer; Pritzlaff, Richard (Frontiers in Environmental Science, 2021)
Historic land degradation is an ongoing threat to the Sky Islands of southern Arizona, US, and northern Sonora, Mexico, an area designated as a globally significant biodiversity hotspot. Land degradation has reduced ecosystem services provisioning, released carbon from disturbed soils into the atmosphere, and significantly diminished resilience to climate change. Private land managers in the region have developed methods to reverse degradation and restore biodiversity and ecosystem function. Land managers have used rock detention structures (RDS) – technology adapted from traditional Indigenous practices in the region – as a tool for reversing desertification and watershed degradation. The structures were installed primarily for erosion control and water management, but they have had positive impacts on multiple biophysical systems. In this study, we analyze watershed-scale installation of RDS as a nature-based solution for climate change mitigation and adaptation. Case studies include four private properties that offer examples of structures that have been in place over a period ranging from 1 to 40 years. We used interview data combined with published data from journal articles and other data collected at these sites. This study documents positive impacts on overall stream flow, reduction in peak runoff during inundation events, and increased sedimentation, which increase resilience to drought, erosion, and flooding. Data suggest potential impacts for climate change mitigation, though further research is needed. In addition, results suggest that watershed restoration with rock detention structures offers a host of co-benefits, including an increase in biodiversity and wildlife abundance, an increase in vegetative cover, and increased surface water provisioning over time to support the land-based livelihoods of downstream neighbors. In the discussion, we consider barriers to replication and scalability using the strategy of the UN Decade on Ecosystem Restoration as a guiding framework. We consider issues of awareness, legislation and policy, technical capacity, finance, and gaps in knowledge.